De notione vocis raḳi'a Gen. I:6 - Lefrén, Laurentius Olavi; Simelius, Matthias; Frenckell, Johan Christopher I (kirjapaino, Turku, 1761-1779); Turun Akatemia; Royal Academy of Turku; Regia Academia Aboensis; Kungliga akademin i Åbo (Aboae : impressit Johannes Christophorus Frenckell, [1775], 1775)
Invokaatio: I.N.J.
Keywords: eksegetiikka; heprean kieli